STUDY PERFORMANCE ANALYSIS OF WHARF BASED ON DISPLACEMENT BASED DESIGN METHOD - ATHARI , EGI
Indonesia is one of the countries with the highest level of earthquake intensity in the world. The epicenter is generally located in the sea so wharf as one of the marine infrastructure supporting the economy must have resistance to the earthquake. There is no regulation in Indonesia that specifically regulates wharf planning especially for earthquake load as in the planning rules of building structures and bridges. So generally wharf design uses one of the building and bridge building rules that may be less precise in setting the parameters of wharf design against the earthquake. In the United States wharf plot against the earthquake is set in ASCE 61-14 Seismic Design of Piers and Wharves. The displacement-based design concept has also been introduced in this regulation in addition to the commonly used style-based design concept. The displacement-based design method is based on displacement as an indication of the level of structural performance in which the performance level of the planned structure is at the level of life safety performance. This study also compares two wharf structure models: detailed model and simplified model. Detailed models take into account soil-structure interaction with soil spring approach whereas simplified model assumes soil-structure interaction with fixity point. The focus of this study is on the use of displacemet based analysis methods and design based on displacement based design which results are verified using time history analysis methods. The results show that the method of analysis of displacemet based and displacement based design has a high degree of accuracy of time history analysis. So this method is very well applied to the planning of earthquake resistant wharf structure using either plumb pile or batter pile. The results of the study also show that the detailed model has better performance than the simplified model when receiving the earthquake load.